[μ-1,1′-Bis(diphenylphosphino)ferrocene]bis{[(Z)-O-ethyl N-phenylthiocarbamato-κS]gold(I)} dichloromethane solvate - Ho, Soo Yei (International Union of Crystallography, 2010)
The binuclear title compound, [Au(2)Fe(C(9)H(10)NOS)(2)(C(17)H(14)P)(2)]·CH(2)Cl(2), which has the Fe atom located on a crystallographic centre of inversion, crystallizes as a 1:1 dichloromethane solvate, which is disordered about a centre of inversion. There is a small deviation from linearity defined by the SP donor set [S1—Au—P1 angle is 175.35 (5) °] which is due to an intramolecular Au⋯O contact [3.080 (5) Å]. The primary intermolecular contacts between binuclear molecules are of the type C—H⋯π, and are arranged so as to form columns in the a-axis direction in which the disordered solvent molecules reside.